Music-Making and Musical Instruments in the Čiurlionis Family Environment - Česnulevičienė Aušra (Meno Istorija ir Kritika)
This study examines for the first time the relationships with music, family musical traditions, and their importance to all family members – but especially to the composer and painter Mikalojus Konstantinas Čiurlionis (1875–1911) – of the two generations of the Čiurlionis family who lived in Druskininkai since the 19th century. Also, for the first time, this study explores the histories of musical instruments belonging to the Čiurlionis. Near Druskininkai, at the church in the village of Kabeliai, an instrument was discovered on which Mikalojus Konstantinas Čiurlionis’ father Konstantinas had played, and archival work was carried out to find supporting evidence. The sources found confirmed the hypothesis held by the author of the article that the church organ in Kabeliai indeed was the instrument used by Konstantinas Čiurlionis, the organist and father of Čiurlionis. It is likely that the future artist and composer Mikalojus Konstantinas also had contact with this instrument. The history of Kabeliai and the discovery of the organ inspired the study of the histories of all musical instruments (both surviving and lost) belonging to the Čiurlionis family and special attention was paid to the exhibits of the M. K. Čiurlionis House-Museum. This article publishes for the first time the authentic memories collected by the author of this work, describing the acquisition histories of the mentioned house-museum exhibits. The result of the research is new facts about music-making in the Čiurlionis household, supplemented, refined, or reconstructed histories of musical instruments used by the Čiurlionis family. Twelve musical instruments were found and described during the study. It was revealed that the Čiurlionis family paid great attention to musical instruments and their quality. Pianos from famous companies in their not very wealthy homes testify that music here was not only educational but also had clear professional ambitions to play classical music and create original (their own) music. The Čiurlionis family was united by the method of learning to play by ear, and the conscious continuation of this family musical tradition is evident in our times at the “Summer of Piano Music in Druskininkai” festival.